Diagnosing Spatial Activation in Historic Public Spaces: An Exploratory Perception–Behavior–Space Study in Guibeicheng, China - Zirui Zhan; Shiyu Lu; Dan Wu; Suhui Zhang (Buildings, 2026)
The regeneration of public spaces in historic urban areas increasingly relies on small-scale and incremental interventions. However, how spatial configuration, observed use, and perceived meaning converge or diverge across specific historic public spaces remains insufficiently understood. This exploratory single-case study uses a Perception–Behavior–Space (PBS) evidence-organizing and diagnostic structure to examine three selected public spaces in Guibeicheng, Wuxi. Evidence was drawn from 24 semi-structured interviews, cognitive maps, short-term multi-period behavioral observations at the three sites, and segment-based space syntax analysis at R = n and at metric radii of 400 m and 800 m. The cross-evidence comparison identified three case-specific patterns: a movement–staying mismatch at Sanyang Square Subway Station, a combined configuration–use and memory–use mismatch at Xue Fucheng’s Former Residence, and perception–behavior convergence despite lower configurational values at Chong’an Temple pedestrian street. None of the six configurational measures reproduced the observed pedestrian-flow ordering, indicating that configurational potential was not consistently aligned with mean pedestrian-flow intensity across the three sites. These patterns informed a case-derived interpretive model organized around everyday-use triggering, activity amplification, narrative anchoring, actor coordination, and governance enablement. The PBS evidence structure supports transparent cross-evidence diagnosis and the development of case-informed planning implications for historic public-space regeneration.